KEPASTIAN HUKUM BAGI PARA PIHAK PEMEGANG SURAT TANDA BUKTI ATAS TANAH BERUPA SERTIFIKAT HAK MILIK DITINJAU DARI HUKUM AGRARIA: (Studi Putusan Pengadilan Negeri Sungailiat Nomor 03/Pdt.G/2012/Pn.Sgt) - Muhammad, Naufal; Agustian, Rio Armanda; Salfutra, Reko Dwi (Fakultas Hukum Universitas Bangka Belitung, 2018)
Verdict Sungailiat Court Number 03/Pdt.G/2012/PN.Sgt in the verdict has stated the defendant (Feng Jung) has committed acts againts the law by certifying a plot of land to a National Land Agency of Bangka Regency on the Right Certificate Number 2305 was issued by the National Land Agency if Bangka Regency in 2003, but was sued by the plaintiff (Tjong Ana) in 2012. The results of research, Paragraph 32 Sentence 2 of Government Regulation Number 24 of 1997 have been fulfilled by defendant in conducting process of land registration of Certificate of Property Number 2305 so that this provision is absolutely to run and about absolute authority to run about absolute authority of judge, that a judge of a Public Court is not authorized to declare a Certificate of Property Number 2305 has no legal force, and certificate that is a powerful evidentiary tool has become an absolute if element of Paragraph 32 Sentence 2 of Government Regulation Number 24 of 1977 has been fulfilled.